Chikungunya infection: self-reported rheumatic morbidity and impaired quality of life persist 6 years later. (July 2015) - Marimoutou, C.; Ferraro, J.; Javelle, E.; Deparis, X.; Simon, F.
Abstract: This study presents the 6-year follow-up of French gendarmes exposed to the chikungunya (CHIK) infection in 2006 on Reunion Island. The aim was to see to what extent the subjective health differences observed in 2008 (30 months after infection) between CHIK infected (CHIK+) and noninfected (CHIK-) gendarmes still persisted in 2012, and to investigate a possible return to a pre-CHIK health status for CHIK+ subjects. Gendarmes were contacted by mail in 2012 and asked to complete a self-questionnaire asking for morbidity, health care and medicines consumption since the last follow-up in 2008. Quality of life (QoL) after 6 years was evaluated using the SF-36 scale. In comparison with CHIK- subjects (n = 171), CHIK+ (n = 81) presented with higher rheumatic but also nonspecific morbidity such as headaches and fatigue associated with a large psychological impact, frequent depressive moods and social disabilities, leading to a significant impairment of the QoL and higher health care consumption. When restricted to CHIK+ subjects, comparing the data with that of 2008 showed persistent but decreasing self-reported rheumatic morbidity, and an increase over time of chronic discomfort (headache, fatigue) and depressive moods, resulting in no overall improvement in QoL. Despite possible cohort attrition bias, the comparability of CHIK+/CHIK- subjects allows the assumption of a long-term impact of CHIK infection with less chance of returning to a previous health status. Although these results may be specific to the 2006 virus strain, we recommend that public health strategies in the epidemic-prone countries include a response to the consequences of chronic post-CHIK disorders.